1987
DOI: 10.1073/pnas.84.10.3254
|View full text |Cite
|
Sign up to set email alerts
|

An insulin-like growth factor (IGF) binding protein enhances the biologic response to IGF-I.

Abstract: The insulin-like growth factors IGF-I and IGF-ll circulate in blood bound to carrier proteins. The higher molecular mass IGF-binding protein complex (150 kDa) is composed of subunits, and one subunit that forms this complex is growth hormone dependent. In addition, many cell types and tissues secrete another form of IGF binding protein that is not growth hormone dependent. Both forms of the IGF binding protein are believed to inactivate the IGFs and to function as delivery systems to tissues. This conclusion w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
284
2
3

Year Published

1989
1989
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 642 publications
(298 citation statements)
references
References 21 publications
9
284
2
3
Order By: Relevance
“…IGF-BP I and IGF-BP III have been shown to inhibit or enhance the action of the IGFs depending on the culture conditions (16)(17)(18). These findings are consistent with a role for BPs in regulating the responsiveness of cells to IGFs.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…IGF-BP I and IGF-BP III have been shown to inhibit or enhance the action of the IGFs depending on the culture conditions (16)(17)(18). These findings are consistent with a role for BPs in regulating the responsiveness of cells to IGFs.…”
supporting
confidence: 78%
“…At each step during the purification of BP, aliquots of fractions were diluted with DMEM containing 1 mg of bovine serum albumin per ml and used for the following assays. (i) BP assay: This assay was based on the principle that polyethylene glycol (PEG) precipitated the large molecular weight BP-IGF complex and not the small molecular weight IGF (18). Briefly, 50 p.1 of sample was incubated with 25,000-50,000 cpm of 1251-labeled IGF-I or IGF-II (1251-IGF-I or 125I-IGF-II) for 60 min at room temperature in 0.1 M Hepes/0.…”
Section: Methodsmentioning
confidence: 99%
“…Recent evidence, however, suggests that the biologic action of IGF-I is strongly modified by the relative concentrations of its binding proteins in plasma, amniotic fluid, and a variety of tissues (27)(28)(29)(30)(31)(32). Thus, a measurement in blood or tissue of the IGF-I concentration after removal of the binding proteins gives only one index of the biologic action of this growth factor.…”
Section: Resultsmentioning
confidence: 99%
“…BPs have been shown to inhibit the effects of IGF-I and IGF-II on fibroblast DNA synthesis (Knauer & Smith, 1980). Binding of these proteins to cell surfaces increases the binding of IGF-I to its receptor (Clemmons et al, 1986) and IGF-I BPs have been shown markedly to potentiate the replication of human mouse and chicken embryo fibroblasts in response to IGF-I stimulation (Elgin et al, 1987). Hence the production of IGF-I BPs by SCLC cells raises the possibility that these proteins similarly modulate the mitogenic responsiveness of SCLC to IGF-I stimulation.…”
Section: Detection Of Immunoreactive Igf-i In Cell Conditioned Mediamentioning
confidence: 99%